2002
DOI: 10.1074/jbc.m208924200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Activity of AP2α Mediated through a Direct Interaction with p53

Abstract: The AP2 transcription factor family is a set of developmentally regulated, retinoic acid inducible genes composed of four related factors, AP2␣, AP2␤, AP2␥, and AP2␦. AP2 factors orchestrate a variety of cell processes including apoptosis, cell growth, and tissue differentiation during embryogenesis. In studies of primary malignancies, AP2␣ has been shown to function as a tumor suppressor in breast cancer, colon cancer, and malignant melanoma. In cell culture models, overexpression of AP2␣ inhibits cell divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
77
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 56 publications
14
77
1
Order By: Relevance
“…3 and lanes 3, 5 and 7). Overall therefore, these findings argue against an absolute dependence on p53 by TFAP2A in upregulating p21cip expression 15,16 and instead agree with observations in HeLa cells, which are functionally null for p53, where CDKN1A was also shown to be positively regulated by TFAP2A.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…3 and lanes 3, 5 and 7). Overall therefore, these findings argue against an absolute dependence on p53 by TFAP2A in upregulating p21cip expression 15,16 and instead agree with observations in HeLa cells, which are functionally null for p53, where CDKN1A was also shown to be positively regulated by TFAP2A.…”
Section: Resultssupporting
confidence: 66%
“…15,16 Partial support for these data has come from an independent study looking at CDKN1A induction following adenovirus mediated overexpression of TFAP2A in derivatives of the HCT116 colon carcinoma line. The degree of p21cip induction upon TFAP2A overexpression in HCT116 p53 -/-cells was significantly reduced compared to that seen with wild-type cells.…”
mentioning
confidence: 99%
“…AP-2a and AP-2g, two members of the AP-2 family, are transcription factors with high homology to each other. It has been reported that there is a physical interaction between p53 and AP-2 proteins (McPherson et al, 2002;Modugno et al, 2002). Most importantly, the functional interaction between these two proteins was discovered and it was demonstrated that both the p53 and AP-2 transcription factors can upregulate p21, arrest cell cycle progression, induce apoptosis and promote tumor death (McPherson et al, 2002;Wajapeyee and Somasundaram, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As a DNA-bindingdefective mutant failed to elicit a comparable effect, p53 DNA-binding ability was essential to exhibit the characteristics of tumor-suppressing function described herein. Even though the presence of p53 can improve AP-2-induced cell killing, AP-2 alone can greatly induce breast carcinoma cell death (McPherson et al, 2002;Wajapeyee and Somasundaram, 2003). Indeed, the fact that AP-2 expression decreased MDA MB-231 cell growth (Supplementary Figure 11) implies that AP-2 may mediate part of p53 function in growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation